THE INFLUENCE CELLULAR PROVIDER SERVICE QUALITY TOWARDS CUSTOMER LOYALTY INDOSAT IN JAKARTA - Dita Puruwita (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2014)
This research aims are to find out how well the service quality of PT Indosat Jakarta, how loyal are the customers, and how far the effect of the service quality toward the customers loyalty Indosat in Jakarta. The category of this research are descriptive and verification with surveys method by using a convenience sampling. The sample sizes is 120 respondents of Indosat customers. Therefore, the data collecting technique used are from secondary data, interview, observation and questionnaires. The result of this research based on hypothetical test indicates that there is a effect between the service quality and the customer loyalty. The conclusion of this research is that the performance of the service quality provided by Indosat is still under the customer expectation. It is suggested to the management of PT. Indosat, to improve and maintain their service quality in the dimension that is regard as important, as well the customer’s loyalty level. Keywords : Service Quality, Customer Loyalty, Indosat